Development of a system for predicting failures of bagging machines - Huliieva, Nataliia; Lishchyna, Nataliia; Pasternak, Viktoriya; Huliieva, Zemfira (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2025)
The reliability and effective operation of machines is a pressing problem for every enterprise, which requires labour intensive systematizationof production processes. The goal is to develop an algorithm and a system for predicting failures of packaging machines based on the analysisof operational indicators. The scientific novelty lies in the integration of statistical data to assess the efficiency of machine operation and predict possible failures, which allows significantly improving maintenance processes and reducing the risks of unforeseen breakdowns. The practical valueis the development of a forecasting system that collects the necessary statistical data and performs forecasting. Based on the collected data, an assessment of the efficiency of work and forecasting of possible failures is carried out. The forecasting system is demonstrated on the example of packaging machines LEMO INTERmat ST-SA 850 of "Tatrafan" LLC. Two research methods were used: calculation (mathematical) and forecasting system (least squares method). The forecasting system provides two ways of presenting data: tabular and graphical. Tabular presentation of data allows filtering information according to various criteria, while graphical display is implemented in the form of diagrams showing the operating time and downtime of machines.The main results are the determined range of probable failure of LEMO INTERmat ST-SA 850 packaging machines, which lies in the range from 9090.5to 12736.5 hours of operation and almost coincides with the manufacturer's warranty period. With timely maintenance, it is possible to increase the lower limit of this interval.